The Exhaustion of Unemployment Benefits in Belgium : Does it Enhance the Probability of Employment? - Bart Leo Wim Cockx; Jean Ries (Institute for the Study of Labor (IZA), 2004)
In Belgium unemployment insurance benefits can only exhaust for one category of workers: partners of workers with (replacement) labour income (mostly women) may loose their entitlement after an unemployment duration ranging from two to eight years, depending on individual characteristics. We contrast three propensity score matching estimators of the impact of benefit exhaustion on the probability of employment: a standard, a before-after and an IV matching estimator. We conclude that benefit expiration is anticipated as from the moment at which the worker is notified, three months in advance, and that it gradually increases the employment rate up to 25 percentage points 14 months after benefit withdrawal.
Keywords: J68; C14; J65; 330; unemployment insurance; programme evaluation; before-after estimator; nonparametric methods; Arbeitslosenversicherung; Reform; Arbeitsangebot; Beschäftigungseffekt; Schätzung; Belgien